2012
DOI: 10.1167/iovs.12-10553
|View full text |Cite
|
Sign up to set email alerts
|

ERK5 Regulates Glucose-Induced Increased Fibronectin Production in the Endothelial Cells and in the Retina in Diabetes

Abstract: PURPOSE. Fibronectin (FN) production and deposition in the tissue is a characteristic feature of diabetic retinopathy. ERK5 is a recent member of the mitogen activated protein kinase (MAPK) family, which plays a critical role in cardiovascular development and maintaining endothelial cell integrity. The aim of this study was to investigate the role of ERK5 signaling in glucose-induced FN overproduction.METHODS. Dermal-derived human microvascular endothelial cells (HMVECs) and human retinal microvascular endothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…ECs, being the first cell type exposed to high blood glucose levels, play a major role in the pathogenesis of chronic diabetic complications [3,29,52]. We carried out in vivo experiments in the retinal capillary ECs.…”
Section: Discussionmentioning
confidence: 99%
“…ECs, being the first cell type exposed to high blood glucose levels, play a major role in the pathogenesis of chronic diabetic complications [3,29,52]. We carried out in vivo experiments in the retinal capillary ECs.…”
Section: Discussionmentioning
confidence: 99%
“…They have found that ERK5 inactivation results in augmented VEGF mRNA expression which contributes to DR-associated neovascularization in rats [ 13 ]. Moreover, they have shown that ERK5 signaling may play a role in the glucose-induced increases in fibronectin production in DR [ 14 ]. Together, these studies and our work highlight a potential role of ERK5 signaling in the pathogenesis of DR. Future studies may examine the ERK5 and its activated form in patients’ specimens to figure out whether ERK5 signaling is similarly important in DR development in humans, like in rodents.…”
Section: Discussionmentioning
confidence: 99%
“…In pulmonary fibrosis Erk5 also appears to be necessary for the production of ECM by fibroblasts and epithelial cells, however, in this case it is associated with Smad3 acetylation; acetylation of Lys19 on Smad3 enhances the binding of Smad3 to DNA (Kim et al, 2013). The activation of Erk5 by glucose in retinal and vascular endothelial cells causes a significant rise in fibronectin expression, a feature of diabetic retinopathy (Wu et al, 2012). Interestingly, in these experiments the effect of Erk5 may be Smad-independent as expression of constitutively active Erk5 was associated with a decrease in Smad2 phosphorylation.…”
Section: Discussionmentioning
confidence: 99%